2020
DOI: 10.2459/jcm.0000000000000992
|View full text |Cite
|
Sign up to set email alerts
|

A simple score to select patients for manual thrombectomy in emergent percutaneous coronary interventions: the DDTA score

Abstract: Background The objective of manual thrombectomy is the removal of occlusive thrombus to improve the results of primary angioplasty. The better understanding of the factors associated with successful manual thrombectomy may provide relevant information regarding thrombus formation and resolution. Methods Observational study of all consecutive patients remitted for emergent percutaneous coronary intervention (PCI) in a single centre. Successful manual thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The DDTA score is based on four variables, three of them might be available before the procedure (DAPT, delay, and age) and the other is obtained after wiring the lesion. In the design cohort, patients consulting with >4 hr since symptoms onset had the lowest rates of successful MT without affecting the final TIMI 3 flow, 11 what clearly suggested that longer time delays induce more thrombus organization.…”
Section: Ddta Score and Mt Outcomesmentioning
confidence: 92%
See 4 more Smart Citations
“…The DDTA score is based on four variables, three of them might be available before the procedure (DAPT, delay, and age) and the other is obtained after wiring the lesion. In the design cohort, patients consulting with >4 hr since symptoms onset had the lowest rates of successful MT without affecting the final TIMI 3 flow, 11 what clearly suggested that longer time delays induce more thrombus organization.…”
Section: Ddta Score and Mt Outcomesmentioning
confidence: 92%
“…The DDTA score is based on four variables, three of them might be available before the procedure (DAPT, delay, and age) and the other is obtained after wiring the lesion. In the design cohort, patients consulting with >4 hr since symptoms onset had the lowest rates of successful MT without affecting the final TIMI 3 flow, 11 what clearly suggested that longer time delays induce more thrombus organization. The effect of Ticagrelor administration before primary PCI was tested in the ATLANTIC trial that failed to demonstrated the primary endpoint of TIMI flow 3 before PCI 29 ; nonetheless, a subsequent subanalysis highlighted that the primary endpoint was reached in patients with delay >53 min 25 .…”
Section: Discusionmentioning
confidence: 92%
See 3 more Smart Citations